Management of Abdominal Gunshot Wounds: Clinical Roles and Responsibilities of Emergency Medical Technicians - Sarwr, Fisal Mohammed Abdullhadi; Meshari Abed Jadullah Hamad; Yasir Ahmed Abdolgader Ghabban; Ahmed Mohammed A. ALmuntashiri; Shabaan Saleh Hussain ALmaslamani; Majed Abdullah Mohammed Asiri; Mashhour Shaqi D ALruwaili; Mohanad Awdah M Albalwe; Murdi Fayed Eid Al-Shammari; Hamoud Nahi Alanazi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Abdominal gunshot wounds (GSWs) represent a severe and high-mortality subset of penetrating trauma. The damage is complex, driven by ballistic principles like kinetic energy transfer and cavitation, and frequently involves multiple intra-abdominal organs. Rapid clinical deterioration from hemorrhage and contamination necessitates an urgent, systematic response. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review outlines the comprehensive management of abdominal GSWs, emphasizing the critical roles of prehospital care, emergency department evaluation, and the integrated, multidisciplinary approach required for optimal patient outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative synthesis of clinical protocols and evidence-based practices is presented, covering pathophysiology, epidemiology, diagnostic evaluation (including the Extended FAST exam and CT imaging), and definitive treatment strategies guided by the patient’s hemodynamic status. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Management begins with prehospital ABCs (Airway, Breathing, Circulation) and hemorrhage control. In the emergency department, hemodynamic status dictates the pathway: unstable patients proceed directly to exploratory laparotomy, while stable patients undergo CT scanning for injury characterization. The EFAST exam is a vital bedside tool for detecting hemoperitoneum in unstable cases. Definitive treatment is overwhelmingly surgical for patients with peritonitis or instability. Non-operative management is reserved for a highly select, stable subset. Core management includes aggressive resuscitation, often with massive transfusion protocols, broad-spectrum antibiotics, and tetanus prophylaxis. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Successful management of abdominal GSWs hinges on rapid recognition, immediate resuscitation, and timely surgical intervention coordinated by a multidisciplinary trauma team. Despite advances, mortality remains high, underscoring the need for efficient trauma systems and ongoing advocacy for primary prevention of firearm violence.